Economic burden of Type 2 diabetes in Iran in 2022 - Amin Mohammadi; Mahshad Goharimehr; Ali Darvishi; Ramin Heshmat; Ensieh Nasli Esfahani; Gita Shafiee; Afshin Ostovar; Rajabali Daroudi (BMC Public Health)
Abstract Background Diabetes mellitus, particularly Type 2 diabetes (T2D), represents a significant global health challenge, with its prevalence steadily rising over the past few decades. This study was conducted with the aim of estimating the economic burden of T2D in Iran. Methods This study employed a prevalence-based approach to estimate the economic burden of T2D and its attributable complications in adults above 20 years old in Iran for 2022. Both direct medical costs and indirect costs were considered in our analysis. Direct medical costs included inpatient and outpatient costs attributable to T2D and its complications, while indirect costs encompassed absenteeism, presenteeism, inability to work, and premature mortality costs due to the disease. Results The findings showed that a total of 5,702,547 people, equivalent to 14.2% of Iranian adults, had T2D. The estimated total direct medical cost of T2D and its attributable complications in Iran in 2022 was 1,879.2 million US dollars (US$-PPP 6,676.9 million). Chronic kidney disease accounted for the largest proportion, followed by ischemic heart disease (IHD), and T2D itself. The total economic burden of T2D and its attributable complications in Iran in 2022, was estimated to be $2,905.7 million US dollars (US$-PPP 10,324.2 million). The direct medical cost constituted the majority of the economic burden (64.7%), while the inability to work due to these health conditions also contributes significantly (28.6%). Absenteeism (2.9%), presenteeism (1.7%), and premature mortality (2.2%) make up smaller proportions of the overall economic impact of T2D and its complications in Iran during that year. Conclusion Our study highlights the significant and diverse economic impact of T2D and its complications in Iran. This burden encompasses not only healthcare-related expenses but also negative impacts on society and productivity, as well as the occurrence of early death. To successfully address this burden, a comprehensive strategy is needed, which includes programs to prevent diabetes, better access to healthcare services, and increased social support for individuals with this long-term condition.